Genomic ancestry as a predictor of haemodynamic profile in heart failure. Issue 2 (26th July 2016) - Bernardez-Pereira, Sabrina; Gioli-Pereira, Luciana; Marcondes-Braga, Fabiana G; Santos, Paulo Caleb Junior Lima; Spina, Joceli Mabel Rocha; Horimoto, Andréa Roseli Vançan Russo; Santos, Hadassa Campos; Bacal, Fernando; Fernandes, Fábio; Mansur, Alfredo Jose; Pietrobon, Ricardo; Krieger, José Eduardo; et al.
Abstract : Objective: The aim of this study is to assess the association between genetic ancestry, self-declared race and haemodynamic parameters in patients with chronic heart failure (HF). Methods: Observational, cross-sectional study. Eligible participants were aged between 18 and 80 years; ejection fraction was ≤50%. Patients underwent genetic analysis of ancestry informative markers, echocardiography and impedance cardiography (ICG). Race was determined by self-classification into two groups: white and non-white. Genomic ancestry was estimated using a panel of 101 348 polymorphic markers and three continental reference populations (European, African and Native American). Results: Our study included 362 patients with HF between August 2012 and August 2014. 123 patients with HF declared themselves as white and 234 patients declared themselves as non-white. No statistically significant differences were found regarding the ICG parameters according to self-declared race. The Amerindian ancestry was positively correlated with systolic time ratio (r=0.109, p<0.05). The thoracic fluid content index (r=0.124. p<0.05), E wave peak (r=0.127. p<0.05) and E/e′ ratio (r=0.197. p<0.01) were correlated positively with African ancestry. In multiple linear regression, African ancestry remained associated with the E/e′ ratio, even after adjustment to risk factors. Conclusions: The African genetic ancestry was associated with worse parameters of diastolic function; the Amerindian ancestry correlated with a worse pattern of ventricular contractility, while self-declared colour was not helpful to infer haemodynamic profiles in HF. Trials registration number: NTC02043431.